To solve this equation, we need to remove the absolute value bars. We can do this by considering two cases.
Case 1: |x-1| = x - 1
In this case, we can rewrite the equation as 6(x - 1) = 36.
Simplifying, we have 6x - 6 = 36.
Adding 6 to both sides, we get 6x = 42.
Dividing both sides by 6, we find x = 7.
Case 2: |x-1| = -(x - 1)
In this case, we can rewrite the equation as 6(-(x - 1)) = 36.
Simplifying, we have -6x + 6 = 36.
Subtracting 6 from both sides, we get -6x = 30.
Dividing both sides by -6, we find x = -5.
Therefore, the solutions to the equation 6|x-1| = 36 are x = 7 and x = -5.
Solve the equation.
6lx-1l=36
1 answer